2018
DOI: 10.1007/978-3-319-91287-5_20
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cerebral Oxyhaemoglobin Levels During and After a Single 20-Minute Bout of Moderate-Intensity Cycling

Abstract: Aerobic exercise produces changes in cerebral oxyhaemoglobin (OHb) concentration; however, the effects of exercise on OHb during the post-exercise period remain to be established. The aim of the present study was to evaluate OHb levels during and after a 20-min bout of moderate-intensity cycling exercise. After a 3-min rest period, 12 healthy volunteers (9 women, 3 men) cycled for 20 min at an intensity corresponding to 50% of their VOmax, after which they were monitored during a 15-min post-exercise rest peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 22 publications
3
19
0
Order By: Relevance
“…Furthermore, previous studies revealed exercise-induced activations in prefrontal cortex (PFC) showing that Hb and HHb levels respond as a function of both exercise load and duration in both experts (Rupp et al 2008) and non-experts (Auger et al 2016; Giles et al 2014; Jung et al 2015). However, previous studies focusing on neurovascular coupling at several intensity levels show that there is no consensus concerning the type of exercise (incremental tests with short stages vs. constant-load exercises), duration of exercise (Giles et al 2014; Tsubaki et al 2016) and intensity (Auger et al 2016; Byun et al 2014; Giles et al 2014; Takehara et al 2017; Tsubaki et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous studies revealed exercise-induced activations in prefrontal cortex (PFC) showing that Hb and HHb levels respond as a function of both exercise load and duration in both experts (Rupp et al 2008) and non-experts (Auger et al 2016; Giles et al 2014; Jung et al 2015). However, previous studies focusing on neurovascular coupling at several intensity levels show that there is no consensus concerning the type of exercise (incremental tests with short stages vs. constant-load exercises), duration of exercise (Giles et al 2014; Tsubaki et al 2016) and intensity (Auger et al 2016; Byun et al 2014; Giles et al 2014; Takehara et al 2017; Tsubaki et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Performing a cognitive task after exercise is potentially ideal as it takes advantage of the heightened cortical activity during recovery. Twenty to 30 min of moderate intensity (50-60% VO 2max ) cycling increased post-exercise cortical oxygenation (i.e., activation), which aligned with improvements in post-exercise executive function performance (Stroop task) (Yanagisawa et al, 2010;Stavres et al, 2017;Tsubaki et al, 2018). Increased PFC oxygenation may be indicative of higher cortical activity and, therefore, greater mental effort leading to improved cognitive processes such as working memory and attention (Herold et al, 2018).…”
Section: Brain Blood Flow and Oxygenationmentioning
confidence: 87%
“…Upon cessation of low-moderate intensity aerobic exercise, cerebral oxygenation remains elevated for up to 30 min (Faulkner et al, 2016;Stavres et al, 2017;Tsubaki et al, 2018). Performing a cognitive task after exercise is potentially ideal as it takes advantage of the heightened cortical activity during recovery.…”
Section: Brain Blood Flow and Oxygenationmentioning
confidence: 99%
“…Based on the drawbacks of EEG and the advantages of fNIRS, fNIRS is currently better suited for measurements of changes in cortical brain activity during physical exercises in unconstrained environments [ 50 , 102 , 103 ]. In fact, fNIRS has been applied during a variety of physical exercises such as juggling [ 104 ], balancing [ 105 , 106 , 107 , 108 , 109 , 110 ], walking (for review see [ 111 , 112 ]), resistance exercises [ 113 , 114 , 115 , 116 ], dancing [ 117 , 118 , 119 ], tai chi [ 120 , 121 ], climbing [ 122 ], synchronized swimming routines [ 123 ], table tennis [ 124 ], running [ 125 , 126 , 127 ], and predominantly during cycling [ 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 ,…”
Section: Which Portable Neuroimaging Tools Can Be Used To Assess Bmentioning
confidence: 99%
“…With respect to the practical application of fNIRS during physical exercising, it is mandatory to emphasize that movement artefacts or systemic physiological artefacts, which occur during physical exercising, influence the accuracy of the brain signal measurement of fNIRS significantly [ 99 , 101 , 149 , 151 , 230 , 231 , 232 , 233 , 234 , 235 ]. To minimize the influence of such signal confounders, appropriate data processing techniques should be applied (e.g., short-separation channel regression (SSR) to account for superficial blood flow [ 99 , 111 , 176 , 235 , 236 ] or SSR in conjunction with accelerometer signals to account for superficial blood flow and motion artefacts in CW-NIRS [ 237 ]).…”
Section: Practical Implementation Of Brain-derived Parameters To Pmentioning
confidence: 99%